Eye Diseases Recent Advances, New Perspectives and Therapeutic Options - Di Lauro, Salvatore; Crespo Millas, Sara; Galarreta Mira, David (IntechOpen, 2023)
In this volume, the reader will find a wide range of extended review chapters from international experts in the field of eye disease, interesting discussions from the field about frequently forgotten diseases, and original research chapters with interesting new ideas about the future of ophthalmology.